Utilising Gamification to Enhance Ambition on Digital Platforms: An Examination of Faculty Members Perspectives in Times of Crisis - Alrashedi , Nashmi Turaikhim; Najmi , Ali Hassan; Alhalafawy , Waleed Salim (Journal of Ecohumanism, 2024)
The utilization of gamification-based digital platforms has been demonstrated to significantly contribute to the optimization of the learning process, fostering robust motivations and a sustained inclination to engage in further learning. Ambition, as a variable, is of significant importance for learners in maintaining their engagement with the educational process during periods of emergency. Nevertheless, despite the significance of this topic, there is a notable scarcity of qualitative studies that have investigated the relationship between gamification-based platforms and ambition. Given the frequency of educational emergencies, it is imperative that scholarly research is conducted to determine how gamification-based platforms can be utilized to promote ambition. This is consistent with the widespread use of gamification as the primary tool for learning in both normal and emergency situations. This study employs a qualitative approach, utilizing a phenomenological methodology to conduct a series of in-depth semi-structured interviews with twelve faculty members who are recognized as experts in the field of gamification and digital platforms. The results identified the most important roles of gamification-based platforms in enhancing ambition, which were represented in four main roles: motivation, planning and goal setting, monitoring, and social interactions. Collectively, these roles enhance ambition. The research recommended that gamification incentives such as points, badges, and chest plates should be employed to enhance users’ desire to learn during any educational emergency.